ChemInform Abstract: Regio‐ and Enantioselective Synthesis of Azole Hemiaminal Esters by Lewis Base Catalyzed Dynamic Kinetic Resolution. Issue 38 (September 2016) - Piotrowski, David W.; Kamlet, Adam S.; Dechert‐Schmitt, Anne‐Marie R.; Yan, Jiangli; Brandt, Thomas A.; Xiao, Jun; Wei, Liuqing; Barrila, Mark T.
Abstract: A modular three‐component dynamic kinetic resolution which affords enantiomerically enriched hemiaminal esters derived from azoles and aldehydes is used to synthesize valuable substituted azoles in a regioselective manner by capping of the equilibrating azole‐aldehyde adduct.